Dynamic signal encoding in the S. cerevisiae calcium response - Dalal, Chiraj (Henry Stewart Talks, 2013)
Calcium and Signaling, Excessive calcium causes cellular stress, Signaling pathways are turned on to combat this stress, In budding yeast, these pathways involve nuclear translocation of transcriptional regulator Crz1, Examination of this regulator shows that nuclear translocation occurs in "bursts", Bursts are quantized and frequency-modulated, Frequency modulation enables proportional expression of downstream target genes, Update interview: Localization pulsing is general, Update interview: Localization pulsing helps regulators control ~1000s of genes at the same time
Updated at 2020/05/15